Genetics and Genomics of Pseudoexfoliation Syndrome/Glaucoma - Schlötzer-Schrehardt, Ursula (Medknow Publications, 2011)
Pseudoexfoliation (PEX) syndrome, one of the most common causes of glaucoma, represents a complex, multifactorial, late-onset disease of worldwide significance. The etiopathogenesis involves both genetic and non-genetic factors. The PEX-specific tissue alterations are caused by a generalized fibrotic matrix process, which has been characterized as a stress-induced elastosis associated with the excessive production and abnormal cross-linking of elastic microfibrils into fibrillar PEX aggregates. The identification of lysyl oxidase-like 1 (LOXL1) as a major genetic risk factor for PEX syndrome and PEX glaucoma further supports a role of elastogenesis and elastosis in the pathophysiology of PEX, as LOXL1 is a pivotal cross-linking enzyme in elastic fiber formation and stabilization. The available data suggest that LOXL1 is markedly dysregulated depending on the stage of the fibrotic process. While transient upregulation of LOXL1 during the early stages of PEX fibrogenesis participates in the formation and aggregation of abnormal PEX fiber deposits, the decreased expression of LOXL1 during the advanced stages of the disease may affect elastin metabolism and promote elastotic processes, e.g. in the lamina cribrosa, predisposing to glaucoma development. However, in view of the low penetrance of the PEX-associated risk variants of LOXL1, other genetic and/or environmental factors must contribute to the risk of developing the PEX phenotype. Some evidence exists for the contribution of additional genes with relatively small effects, e.g. clusterin (CLU), contactin-associated protein-like 2 (CNTNAP2), apolipoprotein E (APOE), glutathione S-transferases (GSTs), and tumor necrosis factor-alpha (TNFA), in certain study populations. Several environmental conditions associated with PEX, such as oxidative stress as well as pro-fibrotic cytokines and growth factors, can regulate expression of LOXL1 and elastic proteins in vitro and may therefore act as co-modulating external factors. Ultimately, both detection and functional characterization of yet unidentified genetic and non-genetic factors may lead to the development of more precise screening tools for the risk of PEX glaucoma.